2023
DOI: 10.2196/39331
|View full text |Cite
|
Sign up to set email alerts
|

A New Digital Health Program for Patients With Inflammatory Bowel Disease: Preliminary Program Evaluation

Abstract: Background Inflammatory bowel disease (IBD) causes chronic inflammation of the gastrointestinal tract. IBD is characterized by an unpredictable disease course that varies greatly between individuals and alternates between the periods of relapse and remission. A low energy level (fatigue) is a common symptom, whereas stress and reduced sleep quality may be the triggering factors. Therapeutic guidelines call for effective disease assessment, early intervention, and personalized care using a treat-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…A similar CSM intervention implemented in individuals with IBS showed reductions in anxiety, depression, abdominal pain, fatigue, and extraintestinal pain and improvements in sleep and quality of life [ 25 - 29 ]. A recently published study of a digital health program in IBD reported promising improvements in stress and energy levels, with a participant retention rate of 40% [ 57 ]. We hope that our approach of incorporating weekly check-ins will lead to higher retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…A similar CSM intervention implemented in individuals with IBS showed reductions in anxiety, depression, abdominal pain, fatigue, and extraintestinal pain and improvements in sleep and quality of life [ 25 - 29 ]. A recently published study of a digital health program in IBD reported promising improvements in stress and energy levels, with a participant retention rate of 40% [ 57 ]. We hope that our approach of incorporating weekly check-ins will lead to higher retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a group of chronic inflammatory conditions of the gastrointestinal (GI) tract characterized by periods of inflammation and remission [ 1 , 2 ]. Typical symptoms of IBD include fatigue, weight loss, bloody diarrhea, tenesmus, abdominal pain/cramps, and urgency to have bowel movements.…”
Section: Introductionmentioning
confidence: 99%